Novel de novo ZBTB20 mutations in three cases with Primrose syndrome and constant corpus callosum anomalies. Issue 5 (21st April 2018) - Alby, Caroline; Boutaud, Lucile; Bessières, Bettina; Serre, Valérie; Rio, Marlene; Cormier‐Daire, Valerie; de Oliveira, Judith; Ichkou, Amale; Mouthon, Linda; Gordon, Christopher T.; Bonnière, Maryse; Mechler, Charlotte; et al.
Abstract : Corpus callosum (CC) is the major brain commissure connecting homologous areas of cerebral hemispheres. CC anomalies (CCAs) are the most frequent brain anomalies leading to variable neurodevelopmental outcomes making genetic counseling difficult in the absence of a known etiology that might inform the prognosis. Here, we used whole exome sequencing, and a targeted capture panel of syndromic CCA known causal and candidate genes to screen a cohort of 64 fetuses with CCA observed upon autopsy, and 34 children with CCA and intellectual disability. In one fetus and two patients, we identified three novel de novo mutations in ZBTB20, which was previously shown to be causal in Primrose syndrome. In addition to CCA, all cases presented with additional features of Primrose syndrome including facial dysmorphism and macrocephaly or megalencephaly. All three variations occurred within two out of the five zinc finger domains of the transcriptional repressor ZBTB20. Through homology modeling, these variants are predicted to result in local destabilization of each zinc finger domain suggesting subsequent abnormal repression of ZBTB20 target genes. Neurohistopathological analysis of the fetal case showed abnormal regionalization of the hippocampal formation as well as a reduced density of cortical upper layers where originate most callosal projections. Here, we report novel de novo ZBTB20 mutations in three independent cases with characteristic features of Primrose syndrome including constant CCA. Neurohistopathological findings in fetal case corroborate the observed key role of ZBTB20 during hippocampal and neocortical development. Finally, this study highlights the crucial role of ZBTB20 in CC development in human.